Improving Skill Indonesian language in 4th grade Elementary School Students of the Macro Role Playing Approach - Aswasulasikin Aswasulasikin; Sri Pujiani; Marisa Apnika (IJE : Interdisciplinary Journal of Education, 2023)
Through the use of role-playing, this study seeks to improve 4th-grade pupils' command of the Indonesian language. Students from SDN 1 Waringin in the fourth grade make up the research subjects. The role-playing technique is expected to enhance students' command of the Indonesian language, according to the study's action hypothesis. The study, which was conducted as a classroom action research project, spans three cycles. The outcomes show that the role-playing method can successfully increase students' command of Indonesian vocabulary, as indicated by their (1) better and fluent pronunciation of vocabulary, and (2) improved comprehension and application of vocabulary, progressing with each cycle. The following findings may be taken from the conducted research and discussion regarding the application of the macro role-playing learning approach to increase Indonesian vocabulary among 4th grade students at SDN 1 Waringin: The implementation of the macro role-playing learning method can enhance learning outcomes in the subject of Indonesian language, specifically in the material of student interviews for 4th-grade students in Waringin. The research findings indicate that in Cycle I, the average class score was 74.5, although it had not yet reached the defined classical mastery level of 80%, achieving a classical mastery percentage of 75%. Meanwhile, in Cycle II, there was an increase in the average class score to 86.75, with a classical mastery rate of 92%.Bagian Atas Formulir